Surprises from Ukraine: Democracy moves out and Russia moves in - Susan Stewart (Stiftung Wissenschaft und Politik (SWP), 2010)
When Viktor Yanukovych won the Ukrainian presidential election in February 2010, there was consensus among most analysts on his probable foreign policy course. It was believed that he would reduce the emphasis on the West and return to a more balanced »multi-vectoral« policy which would include improving relations with Russia. In the domestic sphere, many observers claimed that while there might be some deterioration of press freedom, on the whole pluralism in Ukraine would be preserved, making a significant democratic rollback impossible. In fact, in both these arenas, the pace and the extent of the changes have far outstripped the original predictions, leaving the EU and its member states in something of a quandary as to Yanukovych's goals and intentions
Keywords: 320